A pinch of magic - Thorpe, Kiki; Christy, Jana (New York : Random House, 2014)
Baking-talent fairy Dulcie helps Mia make treats for a neighbohood bake sale but must return to Never Land before they are done, and Mia may not be able to finish without her help.
"A Stepping Stone book"--T.p.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Baked products -- Juvenile fiction